The European Educational Diplomacy: African Perspective - Valentina Gribanova; Veronika Usacheva (Современная Европа, 2025)
Educational diplomacy is a relatively new but actively used tool of the European Union's foreign policy. The EU's educational diplomacy in Africa aims to promote a positive image of Europe and its education system. Historically, favorable conditions have developed for this, since the education systems of the African countries were built by Europeans, teaching is conducted in European languages, and generally curricula reflect the interests of former metropolises. Nevertheless, African countries seek to enhance their education systems using international models, building on the European foundation. At the same time, the struggle of African countries for independence and sovereignty and the need to rethink and overcome the colonial past and neocolonial strategies in the policies by developed countries, can generate tension and distrust between Africa and Europe. The EU offers African countries its educational standards, inter-university programmes, academic and student exchanges. However, there is still a problem of taking into account the opinions of the Africans themselves, in particular what educational programs and specialties are in demand. Furthermore, exchange programs can contribute to brain drain, hindering African development. This article examines the historical roots and contemporary trends of the EU’s educational diplomacy, as well as the attitudes of African countries towards it.